The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2377960817702382
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessed Competence of Experienced Expatriate Nurses in a Rural and Remote Setting

Abstract: We aimed to measure the self-assessed level of competence among nurses working in the public hospitals of Al-Gharbia Region, a remote rural region of United Arab Emirates, and to explore the factors associated with the nurses' self-perceived competency. The Nurse Competency Scale, which measures the self-assessed level of competency of nurses, has been validated in a variety of clinical settings, in facilities of various sizes, and in small and large cohorts. However, its application among an expatriate nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…The UAE is heavily dependent on foreign nurses (El‐Haddad, ), with Emirati nurses comprising only 4% of the nursing workforce. As the UAE will need 8,510 new RNs by 2025 (US‐UAE Business Council, , September), there is a need to recruit and retain skilled, competent and experienced RNs internationally (Aqtash et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The UAE is heavily dependent on foreign nurses (El‐Haddad, ), with Emirati nurses comprising only 4% of the nursing workforce. As the UAE will need 8,510 new RNs by 2025 (US‐UAE Business Council, , September), there is a need to recruit and retain skilled, competent and experienced RNs internationally (Aqtash et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted in South Africa ( (Hassankhani et al, 2017). Also, there is a relationship between perceived competence and frequency of use of a specific competence (Aqtash et al, 2017;Hengstberger-Sims et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…A recent systematic review reported that the NCS is the most widely used instrument to assess generic competence at varying stages of nurses' careers, from students, new graduates, to more experienced nurses (Flinkman et al, ). In the present review, researchers showed that the NCS has been utilized in 30 studies in various countries and translated in different languages; for instance, in Australia (Lima, Newall, Jordan, Hamilton, & Kinney, ), Norway (Wangensteen, Johansson, & Nordström, ), Sweden (Karlstedt, Wadensten, Fagerberg, & Pöder, ), the United Arab Emirates (Aqtash et al, ), and USA (Delaney, Friedman, Dolansky, & Fitzpatrick, ). Although the NCS has been evaluated mostly in terms of its psychometric properties, information about such properties on the translated version is scarce (Flinkman et al, ).…”
Section: Introductionmentioning
confidence: 82%